Peripheral Immune Dysfunction in ESCC with Lymph Node Metastasis: Implications for Preoperative Diagnosis and Prognosis - Yingcen Li; Bin Li; Helian Li; Jingyan Xu; Yali Luo; Jian Gao; Jingxuan Han; Xuling Han; Yiran Zhao; Alin Zhang; Feng Qian (Phenomics, 2026)

PICK1 modulates the proliferation and migration of gastric cancer cells by regulating TLR4 - Kaiqiang Li; Yimin Yang; Yaling Wang; Jing Jin; Qianni Wang; Lina Peng; Aibo Xu; Xuling Luo; Wei Yang; Peng Xu; Bingyu Chen; Ke Hao; et al. (Journal of Zhejiang University-SCIENCE B, 2025)

Humidity-responsive PCL/ICs/PVA pad with directional water transport for fruit preservation - Xuling Song; Zhengfeng Wang; Minxin Zhou; Yuwei Li; Yujie Wei; Yi Luo; Jianfeng Li; Bei Xu; Baijun Shang; Qingshan Duan (Chemical Engineering Journal, 2025)

Highly ammonia-sensitive triboelectric materials enabled by gas-sensing enhancement effect - Yi Luo; Jianfeng Li; Juanxia He; Xuling Song; Bei Xu; Zhijun Zhang; Jiamin Zhao; Yuxin Xie; Yaqi Zhang; Zhengfeng Wang; Baijun Shang; Minxin Zhou; et al. (Chemical Engineering Journal, 2025)

Bionic wood-inspired structure enables aerogel film triboelectric material with humidity adaptation - Ye Zhang; Zhijun Zhang; Weiqing Peng; Juanxia He; Bei Xu; Xuling Song; Jianfeng Li; Yi Luo; Shuangxi Nie; Shuangfei Wang; Dongwu Liang; Qingshan Duan (Chemical Engineering Journal, 2024)

Correction: Deep Immunophenotyping of Human Whole Blood by Standardized Multi-parametric Flow Cytometry Analyses - Jian Gao; Yali Luo; Helian Li; Yiran Zhao; Jialin Zhao; Xuling Han; Jingxuan Han; Huiqin Lin; Feng Qian (Phenomics, 2024)

Death-associated protein 3 in cell death and beyond - Ting Cao; Xuling Luo; Binjiao Zheng; Yao Deng; Yu Zhang; Yuyan Li; Wenwen Xi; Meng Guo; Xuefeng Yang; Zhiyue Li; Bin Lu (Genome Instability & Disease, 2024)

Analysis of the Immune Response by Standardized Whole-Blood Stimulation with Metabolism Modulation - Jialin Zhao; Xuling Han; Helian Li; Yali Luo; Yan Fang; Yun Wang; Jian Gao; Yiran Zhao; Jingxuan Han; Feng Qian (Phenomics, 2024)

Flexible and MOF-808 uniformly assembled polyimide nanofiber membranes with excellent mechanical properties for rapid degradation of chemical warfare agents - Zhikang Cheng; Xiang Li; Li Zhang; Zupei Yuan; Haimin Zheng; Hao Guo; Xu Zhao; Jie Chen; Yu Pan; Xiaoxiao Chen; Yanlai Feng; Zhouai Luo; et al. (Chemical Engineering Journal, 2023)

Threat of soil formation rate to health of karst ecosystem - Chen Ran; Xiaoyong Bai; Qiu Tan; Guangjie Luo; Yue Cao; Luhua Wu; Fei Chen; Chaojun Li; Xuling Luo; Min Liu; Sirui Zhang (Science of The Total Environment, 2023)

Deep Immunophenotyping of Human Whole Blood by Standardized Multi-parametric Flow Cytometry Analyses - Jian Gao; Yali Luo; Helian Li; Yiran Zhao; Jialin Zhao; Xuling Han; Jingxuan Han; Huiqin Lin; Feng Qian (Phenomics, 2023)
Immunophenotyping is proving crucial to understanding the role of the immune system in health and disease. High-throughput flow cytometry has been used extensively to reveal changes in immune cell composition and function at the single-cell level. Here, we describe six optimized 11-color flow cytometry panels for deep immunophenotyping of human whole blood. A total of 51 surface antibodies, which are readily available and validated, were selected to identify the key immune cell populations and evaluate their functional state in a single assay. The gating strategies for effective flow cytometry data analysis are included in the protocol. To ensure data reproducibility, we provide detailed procedures in three parts, including (1) instrument characterization and detector gain optimization, (2) antibody titration and sample staining, and (3) data acquisition and quality checks. This standardized approach has been applied to a variety of donors for a better understanding of the complexity of the human immune system.

Responses of carbon and water use efficiencies to climate and land use changes in China's karst areas - Biqin Xiao; Xiaoyong Bai; Cuiwei Zhao; Qiu Tan; Yangbing Li; Guangjie Luo; Luhua Wu; Fei Chen; Chaojun Li; Chen Ran; Xuling Luo; Huipeng Xi; et al. (Journal of Hydrology, 2023)

High‐resolution mapping of the global silicate weathering carbon sink and its long‐term changes - Chaojun Li; Xiaoyong Bai; Qiu Tan; Guangjie Luo; Luhua Wu; Fei Chen; Huipeng Xi; Xuling Luo; Chen Ran; Huan Chen; Sirui Zhang; Min Liu; et al. (Global Change Biology, 2022)
Climatic and non‐climatic factors affect the chemical weathering of silicate rocks, which in turn affects the CO 2 concentration in the atmosphere on a long‐term scale. However, the coupling effects of these factors prevent us from clearly understanding of the global weathering carbon sink of silicate rocks. Here, using the improved first‐order model with correlated factors and non‐parametric methods, we produced spatiotemporal data sets (0.25° × 0.25°) of the global silicate weathering carbon‐sink flux (SCSF α ) under different scenarios (SSPs) in present (1950–2014) and future (2015–2100) periods based on the Global River Chemistry Database and CMIP6 data sets. Then, we analyzed and identified the key regions in space where climatic and non‐climatic factors affect the SCSF α . We found that the total SCSF α was 155.80 ± 90 Tg C yr −1 in present period, which was expected to increase by 18.90 ± 11 Tg C yr −1 (12.13%) by the end of this century. Although the SCSF α in more than half of the world was showing an upward trend, about 43% of the regions were still showing a clear downward trend, especially under the SSP2‐4.5 scenario. Among the main factors related to this, the relative contribution rate of runoff to the global SCSF α was close to 1/3 (32.11%), and the main control regions of runoff and precipitation factors in space accounted for about 49% of the area. There was a significant negative partial correlation between leaf area index and silicate weathering carbon sink flux due to the difference between the vegetation types. We have emphasized quantitative analysis the sensitivity of SCSF α to critical factors on a spatial grid scale, which is valuable for understanding the role of silicate chemical weathering in the global carbon cycle.

A New Indicator for Global Food Security Assessment: Harvested Area Rather Than Cropland Area - Fengjiao Song; Shijie Wang; Xiaoyong Bai; Luhua Wu; Jinfeng Wang; Chaojun Li; Huan Chen; Xuling Luo; Huipeng Xi; Sirui Zhang; Guofeng Luo; Mengqi Yan; et al. (Chinese Geographical Science, 2022)